Mumps virus infection disrupts blood‐testis barrier through the induction of TNF‐α in Sertoli cells. Issue 11 (26th August 2019) - Wu, Han; Jiang, Xing; Gao, Yunxiao; Liu, Weihua; Wang, Fei; Gong, Maolei; Chen, Ran; Yu, Xiaoqin; Zhang, Wenjing; Gao, Bo; Song, Chengyi; Han, Daishu
Abstract : Mumps virus (MuV) has high tropism to the testis and may lead to male infertility. Sertoli cells are the major targets of MuV infection. However, the mechanisms by which MuV infection impairs male fertility and Sertoli cell function remain unclear. The present study elucidated the effect of MuV infection on the blood‐testis barrier (BTB). The transepithelial electrical resistance of MuV‐infected mouse Sertoli cells was monitored, and the expression of major proteins of the BTB was examined. We demonstrated that MuV infection disrupted the BTB by reducing the levels of occludin and zonula occludens 1. Sertoli cells derived from Tlr2 –/– and Tnfa –/– mice were analyzed for mediating MuV‐induced impairment. TLR2‐mediated TNF‐α production by Sertoli cells in response to MuV infection impaired BTB integrity. MuV‐impaired BTB was not observed in Tlr2 –/– and Tnfa –/– Sertoli cells. Moreover, an inhibitor of TNF‐α, pomalidomide, prevents the disruption of BTB in response to MuV infection. FITC‐labeled biotin tracing assay confirmed that BTB permeability and spermatogenesis were transiently impaired by MuV infection in vivo . These findings suggest that the disruption of the BTB could be one of the mechanisms underlying MuV‐impaired male fertility, in which TNF‐α could play a critical role.—Wu, H., Jiang, X., Gao, Y., Liu, W., Wang, F., Gong, M., Chen, R., Yu, X., Zhang, W., Gao, B., Song, C., Han, D. Mumps virus infection disrupts blood‐testis barrier through the induction of TNF‐α in Sertoli cells. FASEB J. 33, 12528–12540 (2019). www.fasebj.org